Emergence delirium in small animals: a first step towards an objective assessment - Mattei, Larissa Irina; Chiavaccini, Ludovica; Spadavecchia, Claudia; Mirra, Alessandro (Frontiers in Veterinary Science, 2025)
IntroductionEmergence Delirium (ED) is a condition characterized by agitation, confusion and disorientation that can occur in human patients during recovery from anesthesia. In veterinary medicine, a similar phenomenon is observed, but the frequency of occurrence and the characteristics of symptoms are not yet well defined. This study aimed to identify ED symptoms in dogs and cats, explore their occurrence, and recognize related factors.Materials and methodsIn this prospective observational study anesthesia providers systematically, recorded symptoms observed in patients during the recovery phase following anesthesia. The study was divided into three phases. Phase 1: a group of six veterinary anesthesiologists created a list of symptoms possibly related to ED in small animals.Phase 2: demographic and anesthesia-related data were collected for dogs and cats undergoing general anesthesia at the veterinary teaching hospital of the University of Bern between May 2022 and January 2023. The occurrence of ED symptoms was analyzed and based on the occurrence of the listed ED symptoms, animals were assigned to 2 groups: NED group (No-ED group; less than four symptoms observed); ED group (four or more symptoms observed). Phase 3: a logistic regression analysis was performed to explore potential associations between ED occurrence and subject or anesthesia related factors.ResultsPhase 1: based on expert agreement, six symptoms were selected: nystagmus, paddling, opisthotonos, uncoordinated/violent movement, vocalization, and biting. Phase 2: data were recorded from 184 animals (139 dogs, 45 cats). The most common ED symptoms occurring were uncoordinated movement (41%), vocalization (36%) and paddling (30%). More than half of the study population (104/184, 57%) showed at least one symptom of ED; 14% (26/184) of the animals were included in the ED group. Phase 3: no association between subject or anesthesia related factors and the occurrence of ED was found in the univariable analysis.ConclusionBased on the proposed list of symptoms, post anesthetic ED seems to occur frequently in small animals. The observations conducted in the present study can help further evaluation of this phenomenon in dogs and cats.